2023
DOI: 10.1038/s41467-023-39153-6
|View full text |Cite
|
Sign up to set email alerts
|

In-situ spectroscopic probe of the intrinsic structure feature of single-atom center in electrochemical CO/CO2 reduction to methanol

Abstract: While exploring the process of CO/CO2 electroreduction (COxRR) is of great significance to achieve carbon recycling, deciphering reaction mechanisms so as to further design catalytic systems able to overcome sluggish kinetics remains challenging. In this work, a model single-Co-atom catalyst with well-defined coordination structure is developed and employed as a platform to unravel the underlying reaction mechanism of COxRR. The as-prepared single-Co-atom catalyst exhibits a maximum methanol Faradaic efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…Based on the different molecules (CoPc and CoPc-NH 2 ), the as-obtained catalysts were denoted as CoPc/G and CoPc/G-NH 2 , respectively. CoPc/G-NH 2 was prepared using our previously reported method. , Briefly, 100 mg of graphene was dispersed in 100 mL of N , N -dimethylformamide (DMF), forming a uniform solution under ultrasonication for 1 h. Then 10 mg of CoPc-NH 2 was added to the above solution with ultrasonic treatment for another 30 min. After that, the mixture was stirred for 48 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the different molecules (CoPc and CoPc-NH 2 ), the as-obtained catalysts were denoted as CoPc/G and CoPc/G-NH 2 , respectively. CoPc/G-NH 2 was prepared using our previously reported method. , Briefly, 100 mg of graphene was dispersed in 100 mL of N , N -dimethylformamide (DMF), forming a uniform solution under ultrasonication for 1 h. Then 10 mg of CoPc-NH 2 was added to the above solution with ultrasonic treatment for another 30 min. After that, the mixture was stirred for 48 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This result is quantitatively consistent with similar studies by Liu and co-workers conducted in a non-flow aqueous H-cell. 31 We interpret this result to mean that the partial pressure of CO must be sufficiently high relative to CO 2 for CO to bind to the catalyst and react to form CH 3 OH. In comparison, when CO 2 was substituted with N 2 , CH 3 OH forms at a much lower P CO of 0.02 atm (Figure 1a)�N 2 does not competitively inhibit CH 3 OH, whereas CO 2 does.…”
Section: ■ Studying the Competitive Inhibition Of Corr By Comentioning
confidence: 99%
“…Multiple reports demonstrate CORR performance with 20−90 mA/cm 2 j CH3OH and >65% FE CH3OH in zero-gap flow electrolyzers. 30,31 The contrast in CH 3 OH production by CoPc under the CO 2 RR and CORR conditions suggests that CO-to-CH 3 OH is largely suppressed by the presence of CO 2 . The suppression is closely related to the relative binding strength of CO and CO 2 to CoPc.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, much work to be done in developing more effective molecular CO reduction catalysts since there are not many studies doing this with GDEbased systems. Photochemical and electrochemical studies have previously shown that methane and methanol can be produced from CO. [112][113][114] Success here would further enable molecular CO reduction catalysts to be combined with technologies like high-temperature electrolysis of CO 2 to CO, which also do not have issues of carbonate formation. Beyond this, molecular active sites can be used for CO 2 xation beyond the simple CO 2 R such as the generation of products with C-N bonds (e.g.…”
Section: Beyond C 1 Chemistrymentioning
confidence: 99%